STRATEGI GURU DALAM MANFAATKAN MEDIA PEMBELAJARAN SELAMA PANDEMI COVID-19 DI SD DENANYAR 1 - Winda Susanti; Ayang Mutiara Kasih Suci; Fathul Fauzi (ICO EDUSHA, 2021)
: Learning media is a tool that can be used by teachers to assist and support learning so that teaching and learning activities become conducive, so that they can achieve the expected goals during learning activities. Therefore, learning media is very important in the world of education in order to achieve educational goals in Indonesia. The purpose of this study is to describe the management of facilities and infrastructure at SD Negeri Denanyar 1. This research method uses a descriptive qualitative approach. The subjects in this study were SD Negeri Denanyar 1, while the object was learning media at SD Negeri Denanyar 1. The conclusion of this study was to determine the use of learning media in teaching and learning activities at SD Negeri Denanyar 1. Keywords: teacher strategy, learning media, pandemic covid-19 References Akbar, Khairul Dkk. 2021. Manajemen Poac Pada Masa Pandemi Covid-19. Jurnal Kependidikan: Lppm Universitas Pendidikan Mandalika Cheppy Sunzuphy. 2011. Media Pembelajaran. Jakarta: Pt. Raja Grafindo PersadaLutfiyah, Strategi Guru Pendidikan Agama Islam Dalam Mengelola Kelas Untuk Meningkatkan Kualitas Pembelajaran Di Smpn 2 Sumbergempol Tulungagung Tahun Ajaran 2016/2017,UIN Satu Tulungagung, 2017Salinan Permendiknas No 24 tahun 2007